Rancang Bangun Alat Deteksi Kualitas Air Tawar untuk Peternakan Ayam Berbasis IoT Bertenaga Sel Surya - Affan Bachri (KOMPUTEK, 2023)
The need for fresh water for drinking water of chickens is enormous, and it is a vital need for chicken farms. Chemically, water quality can be seen from the pH and mineral content in the water. The degree of pH in broiler drinking water is attempted to be neutral with a range of 6.8-7.2. Chickens do not like water with a pH level too low (acidic) or too high (alkaline). In addition, the pH degree of water also directly affects the economic value of cage equipment. Water that is too acidic will be corrosive so that it will negatively affect the equipment of drinking water installations. In addition, acidic water also has an effect on the medical process (vaccinations, vitamins and drugs). The medical process cannot work optimally when accompanied by acidic water consumption. This study seeks to utilize technology to detect the quality of water used in chicken farms. In addition, the energy source uses solar cells with a capacity of 100 Wp. The maximum power produced by solar panels is 58.8 watts, the minimum power captured is 3.2 watts. And the average power is 46.26 watts. the accuracy of the DS18B20 temperature sensor is 98.3%. turbidity sensor reading accuracy of 99.64%. the average accuracy of the pH sensor is 97.5 %.